2018
DOI: 10.1089/jwh.2017.6423
|View full text |Cite
|
Sign up to set email alerts
|

Need for Comprehensive Counseling in Women Requesting Oocyte Cryopreservation

Abstract: Given the increasing use of oocyte cryopreservation, data support that women be extensively counseled at the time they are requesting elective oocyte cryopreservation for future use in the same manner that they are counseled when requesting ART for pursuing an immediate pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…In addition, some of these women may have maternal-fetal risks in terms of pregnancy due to medical problems they have at the time of oocyte resolution. As recommended by Bachman et al, the detailed informing of these patients must be done at the time of oocyte cryopreservation (27).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, some of these women may have maternal-fetal risks in terms of pregnancy due to medical problems they have at the time of oocyte resolution. As recommended by Bachman et al, the detailed informing of these patients must be done at the time of oocyte cryopreservation (27).…”
Section: Discussionmentioning
confidence: 99%
“…Women who choose elective oocyte cryopreservation may address their gynecologist or fertility preservation team, consisting of an embryologist, fertility specialist, and a psychologist or counselor [8]. However, for quality decision-making, they should be informed of the risks of the procedure, benefits and costs, the success rates, long-term outcomes regarding physical health, psychological well-being, currently known data on the health of children born from frozen oocytes, duration of storage of frozen eggs, and sign an informed consent form [2,5,9].…”
Section: Introductionmentioning
confidence: 99%
“…Comparisons between the groups indicated that counseled patients were significantly less depressed at 3 months postoperatively and reported more beliefs in personal control over health. Another study done by Bachmann G et al (2018)4 focused need for comprehensive counseling in women requesting Oocyte Cryo-presentation.Chi-kongL. et al…”
mentioning
confidence: 99%